Detection of Extended Spectrum β-Lactamase and AmpC gene in Escherichia coli Isolated from Pregnant Women in Misurata City (Journal of Humanitarian and Applied Sciences, 2023)
Urinary tract infections (UTI) are the most common bacterial infections during pregnancy. E.coli is the most common organism causing both community as well as hospital acquired UTI. The various patterns of antibiotic consumption in hospital may account for the diversity and spread of β -lactamase resistant enzymes that associated with diseases. Therefore, prevalence of ESBLs producing E.coli in UTI among pregnant women investigated in 300 bacterial isolates. 160 of the isolates were gram positive, while 140 were gram negative. E.coli was the most frequently isolated pathogen (57%). Regarding to antibiotic resistance, all E. coli isolates were (100%) to Ampicillin and Oxacillin, and first-generation Cephalosporin, Cephalexine and Cephradine. They more sensitive to the third and fourth generation of Cephalosporin, which recommended treating UTI among pregnant women. All E.coli isolates screened for ESBLs production by double-disc synergy test and AmpC test for AmpC enzyme. The result revealed (36%) of tested isolates were ESBLs positive, (20%) AmpC positive and (10%) have both ESBLs and AmpC enzymes. CTX-M gene detected using the PCR method, which revealed that 53% of investigated samples were CTX-M positive.
Keywords: Escherichia coli; UTI; pregnancy; ESBLs; CTX-m; PCR